Canva-assisted biotechnology module based on Marsialap Ari’s local wisdom: The endeavor to improve students' creativity skills - Lubis, Jalilah Azizah; Tuah, Sahlan; Adrian, Muhammad; Saputra, Riska; Padhilah, Suci (Universitas Islam Negeri Sumatera Utara, 2023)
The basis of this research is that the teaching materials created by teachers in the Southern Tapanuli area have not incorporated many models based on local wisdom such as Dalihan Natolu and Marsialap ari. These teaching materials can be utilized to evoke students’ cultural values, character, and creativity. Efforts to enhance student creativity in biotechnology learning still need to be implemented, as the learning process is too fast and students’ understanding is still lacking. This research aims to determine whether the module developed is suitable for use as Biotechnology teaching material in high school based on the BNSP assessment criteria. Additionally, it aims to observe the effectiveness of students using a biology module based on local wisdom (Marsialap ari) assisted by the Canva application on biotechnology material as teaching material in learning for the tenth-grade students in SMA/MA majoring in science. This research is a 4D model development research with research procedures that include defining, designing, developing, and disseminating. The research results can be obtained from the data obtained from several validators, both quantitatively and qualitatively, using descriptive statistical analysis calculations. The module validity of 76.6 - 100% is categorized as valid criteria and LKPD content validity of 80 - 93% is categorized as valid criteria. The product of this research is a biotechnology teaching module based on the local wisdom of Marsialap ari for SMA/MA students. The effectiveness of the module was evaluated based on student performance, with an average of 95 categorized as effective and an average of 90.3 categorized as very creative. In conclusion, the Biotechnology module based on Marsialap ari, assisted by the Canva application, is declared valid for use in studying biology and can enhance students’ creativity in learning biology.